Dispute Arising while Claiming Fire Insurance - Agarwal, Neha (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Fire policies cover owners of commercial or industrial property against material damage caused by fire and extra perils. Fire policies cover a wide range of insured properties from small rural sheds to billion dollar high rise buildings. Losses against these policies are dominated by large individual fire losses and other large losses caused by natural peril and manmade events that generate a large number of simultaneous claims.
Keywords: Fire; Policy Holder; Insurance Company